2021
DOI: 10.7150/thno.46655
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA BCYRN1-induced autophagy enhances asparaginase resistance in extranodal NK/T-cell lymphoma

Abstract: Background: Asparaginase (ASP) is the cornerstone drug in the treatment of extranodal NK/T-cell lymphoma (ENKTCL), and the mechanisms of resistance to ASP remain largely unknown. Long non-coding RNAs play important roles in chemotherapy resistance in various cancers. However, the expression of BCYRN1 and its role in ENKTCL still remain unidentified. Methods: Lentivirus-mediated BCYRN1 overexpression and knockdown were performed in SNK-6 cells. Cell autophagy was analyzed by a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…LncRNA SNHG11 aggravates oncogenic autophagy to facilitate cell proliferation, stemness, migration, invasion and epithelial-to-mesenchymal transition in gastric cancer [ 53 ]. LncRNA BCYRN1 -induced autophagy enhances asparaginase resistance in extranodal NK/T-cell lymphoma [ 54 ]. In pulmonary fibrosis, Ni’s group found that silica-induced pulmonary fibrosis is facilitated by lncHOTAIR through the sponging of MIR326 and attenuated by the increased MIR326 expression through the promotion of the autophagy activity of fibroblasts by targeting PTBP1 (polypyrimidine tract binding protein 1).…”
Section: Discussionmentioning
confidence: 99%
“…LncRNA SNHG11 aggravates oncogenic autophagy to facilitate cell proliferation, stemness, migration, invasion and epithelial-to-mesenchymal transition in gastric cancer [ 53 ]. LncRNA BCYRN1 -induced autophagy enhances asparaginase resistance in extranodal NK/T-cell lymphoma [ 54 ]. In pulmonary fibrosis, Ni’s group found that silica-induced pulmonary fibrosis is facilitated by lncHOTAIR through the sponging of MIR326 and attenuated by the increased MIR326 expression through the promotion of the autophagy activity of fibroblasts by targeting PTBP1 (polypyrimidine tract binding protein 1).…”
Section: Discussionmentioning
confidence: 99%
“…mTOR is a major autophagy regulator, and its phosphorylation can restrain autophagy-related protein expression [ 33 ]. Inactivation of PI3K/Akt pathway and its downstream mTOR could increase LC3-II and Beclin-1 expressing, suggesting the induction of autophagy [ 34 ]. Consistent with these studies, we demonstrated that TUG1 depletion repressed TGF-β or BLM-induced PI3K/Akt/mTOR activation in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Peng et al discovered that BCYRN1 was highly expressed in cervical cancer and that miR-138 inhibition increased cervical cancer proliferation and invasion [ 31 ]. In addition, BCYRN1 is upregulated in extranodal lymphomas and may enhance ASP resistance by activating autophagy [ 36 ]. BC200 is expressed at low levels in ovarian cancer and may inhibit tumor cell proliferation [ 32 ].…”
Section: Discussionmentioning
confidence: 99%